ANALISIS KOMPARASI NILAI KONTRAS MICHELSON PADA PENGAMATAN HILAL BERBASIS OPEN COMPUTER VISION - Damanhuri, Adi (ELFALAKY: Jurnal Ilmu Falak, 2023)
Observing the crescent moon to determine the beginning of the Hijri month has important notes in the form of the validity of the observation results and contrast problems. The application of astronomical observation technology and instrumentation can help the crescent moon observation process to increase the validity of observation results and increase contrast, including the use of an Open Computer Vision (OpenCV) based observation system. In OpenCV you can run a multiview menu, which displays several image profiles at once even if you only use 1 (one) camera instrument. Various models and observation systems have been widely applied, but it is necessary to quantify them to see the effectiveness of the observation results. Analysis of the effectiveness of observation results can be done by measuring the resulting image contrast value. From 8 data from observations carried out on 19 July 2023 in Sidarjo (7°27'39.2" S 112°39'23.2" E), with Michelson contrast, a very significant increase in the image contrast value was obtained, namely an average of 0, 90, with the lowest increase of 0.86 and the highest contrast increase of 0.92.